DETECTING BORAX AND FORMALIN CONTENT IN FOOD USING NATURAL INDICATORS - Meli Agustin; Evita Elyanti; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
The use of hazardous additives such as borax and formaldehyde in food remains a serious problem that threatens public health. This practicum aims to detect the presence of borax and formaldehyde in several food samples using natural indicators in the form of turmeric and red dragon fruit solutions. The method used is observing color changes resulting from chemical reactions between the natural indicators and the hazardous substances in the food. Seven samples were tested: meatballs, sausages, nuggets, instant noodles, sauce, Ale-ale drink, and rock sugar powder. The results showed that the meatballs produced a reddish-brown color change in the turmeric solution, indicating the presence of borax. Meanwhile, the Ale-ale drink caused the dragon fruit solution to fade, indicating the presence of formaldehyde. The other five samples tested negative in both tests. This practicum demonstrates that natural indicators can be used as simple, environmentally friendly, and effective early detection tools for identifying hazardous substances in food. Furthermore, this activity also raised students' awareness of the importance of food safety in everyday life.